The mystery at Lilac Inn - Keene, Carolyn (New York : Grosset & Dunlap, 2007)
Teenage detective Nancy Drew finds herself in danger when she sets out to track a jewel thief.
"This new story ... is based on the original of the same title."
Keywords: Drew, Nancy (Fictitious character) -- Fiction; Jewelry theft -- Fiction; Detective and mystery stories, American